2017
DOI: 10.1007/s00018-017-2589-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects on the dendritic arbor occur by microbead versus bath administration of brain-derived neurotrophic factor

Abstract: Proper communication among neurons depends on an appropriately formed dendritic arbor, and thus, aberrant changes to the arbor are implicated in many pathologies, ranging from cognitive disorders to neurodegenerative diseases. Due to the importance of dendritic shape to neuronal network function, the morphology of dendrites is tightly controlled and is influenced by both intrinsic and extrinsic factors. In this work, we examine how brain-derived neurotrophic factor (BDNF), one of the most well-studied extrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 84 publications
2
22
0
Order By: Relevance
“…It is possible Gαi1/3 proteins play a role in TrkB sorting into distinct endosomal compartments essential for the activation of specific signaling cascades that modulate synapse formation and survival and the differentiation of neurons in the CNS. BDNF is a key mediator of activity-dependent dendrite formation (43,44) via PI3K and MAPK signaling (45). In support of the role for Gαi1/3 in BDNF signaling, Gαi1/3 knockdown in hippocampal neurons in vitro (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…It is possible Gαi1/3 proteins play a role in TrkB sorting into distinct endosomal compartments essential for the activation of specific signaling cascades that modulate synapse formation and survival and the differentiation of neurons in the CNS. BDNF is a key mediator of activity-dependent dendrite formation (43,44) via PI3K and MAPK signaling (45). In support of the role for Gαi1/3 in BDNF signaling, Gαi1/3 knockdown in hippocampal neurons in vitro (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Dendrites were assessed as previously described ( Kutzing et al, 2010 ; Langhammer et al, 2010 ; Kwon et al, 2011 ; O’Neill et al, 2017 ) using the most common Sholl analysis, the Inside-Out labeling scheme ( O’Neill et al, 2015 ). We used the “Bonfire” program developed by our laboratory to perform semi-automated Sholl analysis with a 6 μm ring interval starting at 0 μm from the soma.…”
Section: Methodsmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) is a well-known regulator of dendrite morphology ( McAllister et al, 1995 , 1996 ; Baker et al, 1998 ; Horch et al, 1999 ; Jin et al, 2003 ; Segal, 2003 ; Dijkhuizen and Ghosh, 2005 ; Choi et al, 2009 ; Gao et al, 2009 ; Kuczewski et al, 2009 ; Alder et al, 2012 ; Lazo et al, 2013 ; Park and Poo, 2013 ). Previously, our laboratory reported that BDNF alters the dendritic arbor uniquely depending on how it is applied ( Kwon et al, 2011 ; O’Neill et al, 2017 ). In this work, we extend our previous studies by probing how overexpression and intracellular transport and targeting of BDNF mRNA affect dendritogenesis during the active branching period ( Cline, 2001 ; Wong and Ghosh, 2002 ; Charych et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internalisation of receptors is crucial not only for long distance propagation of neurotrophic effects, but also for engaging intracellular interactors enabling the activation of distinct signalling pathways [15,124]. It is critical for local effects relying on the accumulation of signalling molecules at specific locations, as in the case of synaptic assembly sites, branching points on neurites and the leading edge of a migrating precursor [51,53,84,85,125]. Specific mechanisms of internalisation have proved to be particularly important for generating intracellular compartments with distinct signalling capabilities.…”
Section: Roles In Pathologymentioning
confidence: 99%